Drop evaporation of hydrocarbon fluids with deposit formation. (January 2019) - Hänichen, Philipp; Bender, Achim; Voß, Bernhard; Gambaryan-Roisman, Tatiana; Stephan, Peter
Highlights: Deposit formation leads to a strong increase of the initial apparent contact angle. Deposits lead to surface heterogeneities and, increase the drop pinning phase. For lower temperatures brown films are seen, which are washed to the substrate edge. Close to saturation deposition is strong and concentrated at the substrate center. The drop evaporation can be described with an effective diffusive transport. Abstract: The evaporation and deposit formation process of a hydrocarbon drop on a heated aluminium surface is experimentally investigated and compared to a physico-mathematical model. To analyze the effect of wall temperature on deposit formation, the experiments are conducted for three substrate temperatures below, one temperature close to and one temperature above the saturation point for atmospheric pressure. In each experimental run 500 single drops with constant volume are deposited and evaporated successively. The shape evolution of the drops is recorded with a monochrome camera sidewards. The deposited mass is evaluated as well as the contact angle evolution and drop lifetime. The experiments show a strong dependency of the contact angle on the deposit formation and on the wall temperature. With higher wall temperatures and an ongoing deposit formation, the initial contact angles increase and drop lifetime is reduced. The appearing deposits vary from light yellow and highly viscous films to dark brown solid layers and black particles, depending on the applied substrate temperatures. The model based calculations show a possibility to describe the evaporation process with effective diffusive transport.